Clinical outcomes of high-risk infant follow-up program in a tertiary care centre - Kayvan Mirnia; Forouzan Akrami; Behzad Jodeiry; Mohammad Heidarzadeh; Sima Safavinia (Wolters Kluwer Medknow Publications, 2017)
Background: High-risk infant follow-up (HRIF) program is necessary for early detection, timely intervention, and promotion of health outcomes in vulnerable infants, ethically. The present study was carried out to assess the clinical outcomes of the HRIF Program in Alzahra hospital as a tertiary care centre, in Iran. Materials and Methods: In this cohort study, 5840 neonates were born at Alzahra hospital, from June 1, 2011 to 30th February 2012. Among those who were admitted to neonatal intensive care unit (NICU), 253 infants were recruited by census according to HRIs criteria. After doing necessary measurements and family education, information was recorded in HRI health certificate and then entered in the access database for analysis. Results: From 253 eligible HRIs registered, 241 (95%) infants attended the follow-up clinic after discharge. A total of180 cases were recalled for further visits, 110 of which attended the clinic. Anthropometric indices had an increasing trend in the first 6 months of life. There was no significant relation between ages and stages questionnaire (ASQ) results and infant birth weight, height, and head circumference. The ratios of intraventricular hemorrhage (IVH) and retinopathy of prematurity (ROP) were 8.7% and 3.1%, respectively. The incidence of congenital hypothyroidism was 2:341 in HRIs. Conclusions: Although some outcomes, such as ROP, improved in our study compared to similar studies, the findings indicate an impairment of the current follow-up processes and highlight the necessity to modify the current HRIF program. Ethically, we insist on integrating HRIF program in child health services to promote early childhood development.